Electrical Properties of AlN and SiO2 Co-Modified Barium Titanate Lead-Free Piezoelectric Ceramics. Issue 1 (2nd January 2016) - Fei, W. D.; Xu, D.; Li, W. L.; Wang, L. D.; Wang, W.
Abstract : Ba1 - x Al x Ti1 - y Si y O3 - x N x (BA x TS4 N) piezoceramics were prepared by solid-state reaction sintering. The effects of AlN and SiO2 co-doping on the phase structure and electrical properties of BaTiO3 ceramics were investigated and analyzed. The ceramics adopt a tetragonal crystal symmetry accompanied by the appearance of secondary phases Ba2 TiSi2 O8 and Ba4 Ti2 O27 . The results of temperature dependence of dielectric constant indicate that the Curie temperature of BA x TS4 N ceramics is independent of doping content. The BA x TS4 N ceramic for the composition of x = 3% obtains the optimum ferroelectric properties with the remnant polarization (2 P r ) of 14.69 μC/cm 2 and the maximum piezoelectric coefficient ( d 33 ) of 230 pC/N.